Design a small wind tunnel studies for boundary layer experiment / Mohd Effandy Mukhtar - Mukhtar, Mohd Effandy (2005)
Boundary layer theory is an essential knowledge in aerodynamics study. In order to study boundary layer, the appropriate equipments are required. The most popular equipment which often used is a wind tunnel. Because miniature, portable wind tunnels are not commercially available, I am designed a small portable wind tunnel for the Mechanical Engineering Department of Universiti Teknologi Mara. The wind tunnel was designed to deliver air at flow rates ranging from 0 to 25.6 cubic meter per minute by using 1/5 hp tube axial fan. The total pressure drop throughout the miniature, portable wind tunnel is 1.0786 inH20. Air speeds through the 0.0142m2 test section are variable from Om/s to 30m/s. The wind tunnel can incorporate two possible test configurations within the test section. The first utilizes smooth flat plate model, which attach to wall of test section. The second configuration incorporates a flat plate with rough surface. Pressure drop through the 600mm long test section is obtained mechanically with the use of pitot tube and a manometer. Velocity measurements are also obtained with a pitot tube and outputted to the inclined manometer.